DAMPAK SOSIAL GAME ONLINE MOBILE LEGENDS: BANG BANG TERHADAP REMAJA DESA FOGI KECAMATAN SANANA KABUPATEN KEPULAUAN SULA - Florika Angelina; Veronika Salem; Hamdi Gugule (Labor Program Studi Pendidikan Sosiologi, 2021)
Nowadays, Mobile Legends Game is booming in the community, the fans are not indiscriminate, ranging from children to teenagers. Paying attention to the phenomenon of online games and their impacts, which are currently very widespread, the researchers conducted a study that aimed to determine the impact, both positive and negative impacts, from playing the online game Mobile Legends: Bang Bang on Adolescent smartphone users who play smart phones. games. The assessment method used in this research is a qualitative approach. Data collection techniques are more on participatory observation, in-depth interviews, and documentation. The results of research by researchers on adolescents in fogi village confirmed that game players will get good knowledge and experience about technology, especially the internet, can make someone who plays creative and imaginative games, and can relax the mind when bored, the escape for teenagers is only how to play games so that they will get more serenagnan and satisfaction. The negative impact that can be caused is that it can cause addiction so that it can interfere with learning concentration and neglecting duties and responsibilities as a teenager